Pengaruh Bantuan Kartu Indonesia Pintar (KIP) Terhadap Harapan Sekolah di Provinsi Jawa Timur Tahun 2017 - Bondan Satriawan (MediaTrend, 2019)
This study aims to determine and analyze the effect of the Smart Indonesia Card assistance on school expectations in East Java Province. This research is a quantitative research with 2017 SUSENAS data with 496 consonations. The analysis technique used to prove and test the hypothesis proposed is logistic regression technique. The results of this study resulted in that the Smart Indonesia Card (KIP) had a significant and positive effect on school participation and school participation in the previous school year (2015/2016) in the East Java province. In addition, household characteristics, namely the level of education of the head of the household, also significantly and positively influenced school participation and school participation in the previous school year (2015/2016) in the East Java province. Job status variables of the head of the household have a significant and positive effect on school participation but have no significant effect on school participation in the previous school year (2015/2016).